KARAKTERISTIK MORFOLOGI DAN KANDUNGAN MINYAK DUA NOMOR SELASIH HUTAN (Ocimum gratissimum L.) - Sri Wahyuni; Endang Hadipoentyanti; Agus Kardinan (Pusat Penelitian dan Pengembangan Perkebunan, 2005)
Morphological characteristics and oil content of two accession numbers of tree basil (Ocimum gratissimum L.)Accession of essential oil plants can be distinguished based on morphological characters, oil content and its major chemical constituent. In this research, observations on two accession numbers of tree basil were performed to know their differences. Seeds were planted at the nursery, then transplanted to the polybag before their planted in the field. Fivety plants were planted at bedding size 2 x 3 m with 40 x 30 cm spacing. Morphological characters observed were habitus, stem diameter, shape and colour; leaves shape, colour and pubescentness; flower colour, petal colour and panicle arrangement; seed shape, colour and weight. The essential oil was extracted from whole herbs (young stem, leaves and flower) and analyzed their oil physicochemical characters and major oil constituent. Based on morphological characters both accession is difficult to be distinguished exept for their leaf odour. Accession from Serang has less leaves odour compared to accession from Bogor. The oil content and physicochemical characters of the two accessions were most similar but different in the oil chemical constituent. Major chemical constituent of tree basil from Bogor is eugenol (37,04%), sineol (21,44%) and timol (9,67%), mean while major chemical constituent accession from Serang is Sineol (40,03%), eugenol (13,94%) and linalool (11,17%). For the pesticides used, accession from Bogor will be better because it has higher eugenol.